Using Poly(amidoamine) PAMAM-βCD Dendrimer for Controlled and Prolonged Delivery of Doxorubicin as Alternative System for Cancer Treatment - Kendra Sorroza-Martínez; Ignacio González-Sánchez; Raúl Villamil-Ramos; Marco Cerbón; Jorge Antonio Guerrero-Álvarez; Cristina Coronel-Cruz; Ernesto Rivera; Israel González-Méndez (Pharmaceutics)
Background/Objectives: Doxorubicin (Dox) is an anticancer drug used in the treatment of a wide range of solid tumors; however, Dox causes systemic toxicity and irreversible cardiotoxicity. The design of a new nanosystem that allows for the control of Dox loading and delivery results is a powerful tool to control Dox release only in cancer cells. For this reason, supramolecular self-assembly was performed between a poly(amidoamine) (PAMAM) dendrimer decorated with four β-cyclodextrin (βCD) units (PAMAM-βCD) and an adamantane–hydrazone–doxorubicin (Ad-h-Dox) prodrug. Methods: The formation of inclusion complexes (ICs) between the prodrug and all the βCD cavities present on the surface of the PAMAM-βCD dendrimer was followed by 1H-NMR titration and corroborated by 2D NOESY experiments. A full characterization of the supramolecular assembly was performed in the solid state by thermal analysis (DSC/TGA) and scanning electron microscopy (SEM) and in solution by the DOSY NMR technique in D2O. Furthermore, the Dox release profiles from the PAMAM-βCD/Ad-h-Dox assembly at different pH values was studied by comparing the efficiency against a native βCD/Ad-h-Dox IC. Additionally, in vitro cytotoxic activity assays were performed for the nanocarrier alone and the two supramolecular assemblies in different carcinogenic cell lines. Results: The PAMAM-βCD/Ad-h-Dox assembly was adequately characterized, and the cytotoxic activity results demonstrate that the nanocarrier alone and its hydrolysis product are innocuous compared to the PAMAM-βCD/Ad-h-Dox nanocarrier that showed cytotoxicity equivalent to free Dox in the tested cancer cell lines. The in vitro drug release assays for the PAMAM-βCD/Ad-h-Dox system showed an acidic pH-dependent behavior and a prolonged profile of up to more than 72 h. Conclusions: The design of PAMAM-βCD/Ad-h-Dox consists of a new controlled and prolonged Dox release system for potential use in cancer treatment.